Efforts to Improve Class V IPS Learning Outcomes Through the Implementation of the Problem Based Learning Method at State Elementary School - Suharti, Suharti; Rahmadani, Nuzul; Hamzah, Norhayati; Aradi, Bernadett; Fantaye, abayneh Kebede (Cahaya Ilmu Cendekia Publisher, 2025)
Research Objective: To improve students' learning outcomes in social studies. By implementing the Problem Based Learning (PBL) method to help students understand social studies concepts better. Methodology: This research is a Classroom Action Research (CAR) consisting of four stages of activities, namely: (1) planning stage, (2) action implementation stage, (3) observation stage, and (4) evaluation stage and reflection. The research sample was fifth grade students at SDN 143 Tamiai, with research instruments namely observation, documentation and tests. Main Findings: The results of the study showed that in the pre-cycle, students' learning completeness reached 27.58%. There was an increase of 20.69% in the implementation of cycle I. In cycle II, there was an increase of 37.93% or learning completeness of 86.20%. Thus, it is proven that the use of the Problem Based Learning learning model can improve students' learning outcomes. Research Update: This research strengthens the relationship between the Problem Based Learning model and learning outcomes, especially in social studies lessons.